KAJIAN POLITIK PENDIDIKAN ISLAM DALAM PENGELOLAAN PESANTREN - Ismail, Maskuri (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
The study of the dynamics of Islamic boarding school as one of Islamic education model in Indonesia has always attracted attention. Especially if combined with the politics in education. The synergy between the dynamics of Islamic boarding school and the politics growing going to be the center of attention of observers and practitioners of Islamic education. The strategic role of Islamic boarding school in the life of nation and state is not small, even decisive for the state. Therefore, the development of Islamic boarding school education is always in line with the changes that occur in the political system so created education system. Pro and contra of Islamic boarding school as part of or stand alone is no longer crowded like the past. There is nodichotomy in a private education (Islamic boarding school) and education organized by the state. Its existence becomes synergy in developing and advancing the state. That is the importance of combining the journey of dynamics of Islamic boarding school and politics growing.